The Use of Carbonate-Clay Flour, Sewage Sludge and Waste Sulfate Sulfur as Fertilizer Agents - Ireneusz Skuta; Beata Kołodziej; Barbara Filipek-Mazur; Jacek Antonkiewicz (Resources, 2025)
Macro- and microelements in waste can be returned to the soil as fertilizers and their sustainable use can reduce the need to extract natural resources. For example, the use of carbonate-clay flour, sewage sludge and waste sulfate sulfur to improve soil properties enables the natural recycling of the nutrients contained in these materials. Soil physicochemical properties with the application of waste and the bioavailability of nutrients and trace elements were assessed before and after a 3-month incubation period. This study showed that when carbonate-clay flour was applied alone or together with sewage sludge and waste sulfur, it improved the properties of the soil, inducing a reduction in acidification and an increase in the content of available P, K and Mg. Sewage sludge also provided Zn, Cu, Ni and Cr in addition to organic carbon. Sulfate did not cause soil acidification. The results indicate that the use of carbonate-clay flour alone, as well as with the addition of sewage sludge and sulfate sulfur, can be recommended for the deacidification of soil and serve as a remediation tool for, for example, the precipitation of chemical pollutants. The valorization of the waste used fits into the circular economy approach.